Answer:
a. -5
b.-5
c.-5
Step-by-step explanation:
In order to find the average rate of change of a function , we divide the change in the output value by the change in the input value.
Generally, the average rate of change (ARC) on an ecuatios between two points (x1,f(x1)) and (x2,f(x2)) is
- ARC = [f(x2)-f(x1)]/ (x2-x1)
<em>In case a)</em>
f(-1)= -5*(-1)-8=5-8= -3 f(3)= -5*3-8= -23
Then ARC= (-23-(-3))/(3-(-1))=-20/4=-5
<em>In case b)</em>
f(a)= (-5a-8)
f(b)= (-5b-8)
Then ARC= [(-5b-8)-(-5a-8)]/(b-a)= (-5b+5a)/(b-a)= -5(b-a)/(b-a)= -5
<em>In case c)</em>
f(x)= -5x-8
f(x+h)= -5(x+h)-8= -5x-5h-8
then ARC= [(-5x-5h-8)-(-5x-8)]/(x+h-x) =-5h/h= -5
Answer:
○
Step-by-step explanation:
3 → 13 − 16
I am joyous to assist you anytime.
10 >= 7 + 3x -4x+9<=1
-7 >= -7 - subtract 7 -9<=-9 - Subtract 9
__________ ___________
3 >=3x - divide by 3 -4x<=-8 - divide by -4
x>=1 x<=2
Answer: C) $480
Step-by-step explanation:
Given: Jose invested $5000 into a fund with an interest rate of 4.8%.
Therefore, Principal amount (P)$5000
Rate of interest = 4.8%
In decimal rate of interest(r)=0.048
Time (t)= 2 years
We know that the simple interest is given by
Hence, the interest after 2 years = $480
Answer:
Step-by-step explanation: